Dietary probiotic Lactobacillus sp. for yellow tail tetra Astyanax bimaculatus reared at high and low stocking densities improved the feed conversion ratio, final yield, and intestinal morphometry - Marco Shizuo Owatari; Nicollas Breda Lehmann; Marina de Oliveira Pereira; Andressa Vieira de Moraes; Adolfo Jatobá (Ciência Rural)
ABSTRACT: The present study evaluated the growth performance, survival, feed conversion ratio, intestinal morphometry, and final yield of yellow tail tetra Astyanax bimaculatus after dietary supplementation with the probiotic Lactobacillus sp. at a concentration ≥ 1.0 × 107 CFU g-1. For this purpose, 480 fish (0.25 ± 0.03 g) were randomly distributed into 16 experimental units of 20 L (30 fish per unit) and divided into a two-factor experimental design (2×2). The fish were subjected to four treatments for 90 days: low stocking density (0.75 fish L-1) and fed a probiotic diet (LP); low density and fed a control diet (LC); high stocking density (2.25 fish L-1) and fed a probiotic diet (HP); and high density and fed a control diet (HC). Density did not influence the growth performance or carcass quality of yellow tail tetra. However, fish fed with a diet containing Lactobacillus sp. showed a significant increase in survival in the HP group as well as in FCR and the final yield index, which are important production indicators for the aquaculture industry. Furthermore, the intestinal histomorphometric analysis of fish from the probiotic group revealed improvements at both densities. The data from the present research strengthen the perspectives of this species in aquaculture, in addition to confirming the benefits of Lactobacillus sp. as a feed additive for the aquafeed industry.